2011
DOI: 10.1128/aac.00009-11
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Patients Harboring Extended-Spectrum-β-Lactamase-Producing Enterobacteriaceae on Hospital Admission: Derivation and Validation of a Scoring System

Abstract: Increases in community-acquired infections caused by extended-spectrum-␤-lactamase (ESBL)-producingEnterobacteriaceae have important implications for hospital infection control and empirical antibiotic therapy protocols. We developed and validated a tool for identifying patients harboring these organisms at hospital admission. We retrospectively analyzed chart data for 849 adult inpatients

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
136
2
4

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 150 publications
(153 citation statements)
references
References 35 publications
11
136
2
4
Order By: Relevance
“…In addition, stratification of patients with Gram-negative BSI based on prognosis as predicted by BSIMRS provides a tool to improve the use of empirical antimicrobial agents in patients with suspected BSI due to Gram-negative bacilli that harbor antimicrobial resistance genes. Prior studies have identified patients at risk of BSI due to Pseudomonas aeruginosa and fluoroquinolone-resistant and ESBL-producing Enterobacteriaceae based on the number of individual risk factors for antimicrobial resistance or the summation of the weighted score for each risk factor (17)(18)(19)(20). The decision to expand antimicrobial coverage may appear less complex in patients with no or multiple risk factors for antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, stratification of patients with Gram-negative BSI based on prognosis as predicted by BSIMRS provides a tool to improve the use of empirical antimicrobial agents in patients with suspected BSI due to Gram-negative bacilli that harbor antimicrobial resistance genes. Prior studies have identified patients at risk of BSI due to Pseudomonas aeruginosa and fluoroquinolone-resistant and ESBL-producing Enterobacteriaceae based on the number of individual risk factors for antimicrobial resistance or the summation of the weighted score for each risk factor (17)(18)(19)(20). The decision to expand antimicrobial coverage may appear less complex in patients with no or multiple risk factors for antimicrobial resistance.…”
Section: Discussionmentioning
confidence: 99%
“…MRSA, Clostridium difficile, ESBL-producing and fluoroquinolone-resistant Enterobacteriaceae. 6,21,[48][49][50][51][52] Other risk factors for infection with resistant bacteria are listed in Table 2. 6,9,[18][19][20][21][22]26,31,35,[37][38][39][40][41][42][43]51,53,54 In addition, and, independently of the risk of bacterial resistance, the patient's clinical presentation may also predict a severe clinical course or further deterioration.…”
Section: Importance Of Appropriate Initial Antibiotic Therapy In Febrmentioning
confidence: 99%
“…La última identificó como factores de riesgo a las variables de hospitalización reciente (< 12 meses), índice de Charlson, uso reciente de antimicrobiano (≤ 3 meses, β-lactámicos o fluroquinolonas), cateterización urinaria reciente y edad (≥ 70 años) 28 . Sus hallazgos son muy similares a los del presente estudio.…”
Section: Artículo Originalunclassified